Five Years of Reef Check Monitoring Data for Tioman, Perhentian and Redang Island - Hyde, Julian; Chen, Sue Yee; Chelliah, Alvin (Malaysian Journal of Science, 2013)
The Reef Check survey methodology was designed for use by non-scientists to assess the health of coral reefs. The methodology focuses on the abundance of particular coral reef organisms that best refl ect the condition of the ecosystem and that are easily recognisable to non-scientists. Selection of these “indicator” organisms was based on their economic and ecological value, their sensitivity to human impacts and ease of identifi cation, allowing large numbers of non-scientists to participate in surveys. Indicators include a broad spectrum of fi sh, invertebrates and substrate categories that refl ect human activities such as fi shing, collection or pollution. The fi rst global survey programme in 1997 provided scientifi c confi rmation that coral reefs were facing a major crisis on a global scale. Since 2007, Reef Check Malaysia has conducted an annual Reef Check survey programme of Malaysia’s coral reefs. The paper presents an analysis of fi ve years of data (2007-2011) collected from over 100 survey sites in both Peninsular and East Malaysia. Changing populations of fi sh and variations in live coral cover highlight local impacts on coral reefs, providing valuable information for managers and scientists. Data can be used to manage local threats to coral reefs, and contributes to building coral reef resilience. (Keywords: Reef Check, coral reefs, survey, Tioman, Perhentian, Redang)